Pengalaman dan Strategi Mantan Pasien Covid-19 dalam Menghadapi Stigmatisasi Masyarakat di Bangkalan Madura - Fitria Dayanti; Fransiscus Xaverius Sri Sadewo (Jurnal Community, 2022)
Covid-19 has a social effect. Various new views on Covid-19 patients, families and medical personnel have created various stigmas in society. Giving stigma is certainly mentally inviting because it can have an atmosphere effect, both for the mental health of patients and families as well as the process of stopping the spread of the virus itself. This study aims to explore and identify the experiences and strategies of former Covid-19 patients in dealing with the stigmatization of society. The method in this research is qualitative by using a phenomenological approach. The results showed that Covid-19 gave rise to labeling and stigma on Covid-19 patients and their families. The provision of stigma by the community is carried out by labeling or stereotyping, separation, elimination of status, and even discriminatory attitudes. The strategies used by former Covid-19 patients in dealing with community stigmatization are increasing communication and increasing the intensity of interaction between family members, staying at home, not visiting (conducting regular visits), strengthening and motivating fellow family members, not doing motivational activities and negative treatment of society, surrender, sincerity, and be patient and pray. These strategies are used to maintain the physical, mental, and psychological health of patients and family members.